Blockchain in sports : insights - Thomas, Stuart; Tierney, Kieran D.; Potts, Jason (Routledge, 2025)
"This is the first book to examine the impact of blockchain technology on the business of sport. It introduces the fundamentals of blockchain, and explores its current and prospective applications in sport, as well the implications - both positive and negative - of blockchain for the future of the global sport industry. The book opens by explaining how blockchain works, assuming no prior knowledge on the part of the reader, and introduces the most important aspects of blockchain in practice, such as Non Fungible Tokens (NFTs) and Decentralised Autonomous Organisations (NAOs), as well as new ways of gathering data, such as The Internet of Things, that interact with blockchain infrastructure. The book then examines blockchain in relation to functional areas of sport business, including marketing and fan engagement, athlete contracting and doping records, sport betting markets, fantasy leagues and esports. This is essential reading for anybody with an interest in sport business and management, e-commerce, or the impact of new technologies on the economy and wider society"-- Provided by publisher.
"Routledge Focus"--Cover.
Keywords: Sports -- Technological innovations.; Blockchains (Databases); Internet of things.; Sports administration -- Technological innovations.; elektronické knihy; electronic books